Independent Association of Muscular Strength and Carotid Intima-Media Thickness in Children - Melo, X.; Santa-Clara, H.; Santos, D. A.; Pimenta, N. M.; Minderico, C. S.; Fernhall, B.; Sardinha, L. B. (International Journal of Sports Medicine, 2015)
The aim of this cross-sectional study was to examine the influence of muscular strength on carotid intima-media thickness (cIMT) in children, controlling for the effect of cardiorespiratory fitness (CRF) and central adiposity and to examine if differences among muscular strength tertiles translate to physiological differences. We assessed cIMT of the common carotid artery in 366 children between 11–12 years of age (191 girls). Measures included cIMT assessed with high-resolution ultrasonography, a maximal handgrip strength test, body fat mass and lean mass from DXA and CRF determined using a maximal cycle ergometer test. Association between muscular strength and cIMT adjusted for CRF and central adiposity, as measured by trunk fat, was tested with multiple linear regression analysis. Differences in risk factors among muscular strength groups were tested with ANOVA. The Muscular Strength Index (MSI) was inversely associated with cIMT independently of CRF and central adiposity (p<0.05). The low MSI group had the highest values of cIMT, waist circumference and systolic blood pressure and the lowest CRF (p<0.05). There was an inverse and independent association between muscular strength and cIMT. Low muscular strength was associated with higher levels of cardiovascular disease risk factors in children.
Keywords: handgrip; cardiorespiratory fitness; central adiposity; intima-media thickness